Deficient Letter-Speech Sound Integration Is Associated With Deficits in Reading but Not Spelling - Kemény, Ferenc; Gangl, Melanie; Banfi, Chiara; Bakos, Sarolta; Perchtold, Corinna M.; Papousek, Ilona; Moll, Kristina; Landerl, Karin (Frontiers in Human Neuroscience, 2018)
Efficient and automatic integration of letters and speech sounds is assumed to enable fluent word recognition and may in turn also underlie the build-up of high quality orthographic representations, which are relevant for accurate spelling. While previous research showed that developmental dyslexia is associated with deficient letter-speech sound integration, these studies did not differentiate between subcomponents of literacy skills. In order to investigate whether deficient letter-speech sound integration is associated with deficits in reading and/or spelling, three groups of third graders were recruited: (1) children with combined deficits in reading and spelling (RSD, N = 10), (2) children with isolated spelling deficit (ISD, N = 17), and (3) typically developing children (TD, N = 21). We assessed the neural correlates (EEG) of letter-speech sound integration using a Stroop-like interference paradigm: Participants had to decide whether two visually presented letters look identical. In the case of non-identical letter pairs, conflict items were the same letter in lower and upper case (e.g. ‘T t’), while non-conflict items were different letters (e.g. ‘T k’). In terms of behavioural results, each of the three groups exhibited a comparable amount of conflict-related reaction time increase, which may be a sign for no general inhibitory deficits. Event-related potentials, on the other hand, revealed group-based differences: The amplitudes of the centro-parietal conflict slow potential were increased for conflicting items in typical readers as well as the ISD group. Preliminary results suggest that this effect was missing for children with RSD. The results suggest that deficits in automatized letter-speech sound associations are associated with reading deficit, but no impairment was observed in spelling deficit.